Citra Masyarakat Dan Wisatawan Terhadap Daya Tarik Wisata Di Kota Semarang - Mengku Marhendi (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2022)
Tourism is a social phenomenon involving humans, groups, organizations and culture. Despite the fact that initially tourism was seen more as an economic activity, and the main goal of developing tourism was to gain economic benefits for both the community and the country. But in its journey tourism is not only an economic problem, but also a social, cultural and political problem. Therefore, as an activity that is very dynamic and a phenomenon that is complex and has a major influence on human life and society, tourism needs to be studied and understood continuously in a comprehensive manner from various perspectives of scientific disciplines, one of which is social science. This study seeks to analyze the image of the public and tourists towards tourist attractions in the city of Semarang. The subjects of this study were 8 (eight) local people and 8 (eight) tourists. Collection and processing of data using qualitative research methods. The results found that people and tourists: (1) observe tourist attractions in detail to complete their curiosity; (2) feel that a tourist attraction has beautiful scenery that creates a feeling of pleasure, comfort and awe; (3) visiting a tourist attraction with a plan, circling the entire area of ​​the tourist attraction and intending to visit it again; (4) image of a tourist attraction: original and has natural beauty, various attractions are available, there are features that make the tourist attraction rare and unique, and there are facilities and infrastructure that support the tourist attraction to become a worthy tourist spot visited and visits to tourist attractions in the sense of benefit.